2023
DOI: 10.2147/jpr.s415642
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Alleviated Paclitaxel-Induced Peripheral Neuropathy by Interfering with Astrocytes and TLR4/p38MAPK Pathway in Rats

Haibin Shi,
Minmin Chen,
Caihong Zheng
et al.

Abstract: Paclitaxel-induced peripheral neuropathy (PIPN) constitutes a refractory and progressive adverse consequence of paclitaxel treatment, causing pain and sensory anomalies in cancer survivors. Although the gut-brain axis is involved in multiple disorders including cancer, its impact on peripheral pain conditions remains elusive. Thus, we assessed the importance of gut microbiota and related mechanisms in PIPN. Methods: By implementing fecal microbiota transplantation (FMT) in a rat PIPN model (ie, rats treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…FMT also alleviated Paclitaxel-Induced Peripheral neuropathy in rats by interfering with the TLR4 pathway [80].…”
Section: Chemotherapy-induced Peripheral Neuropathymentioning
confidence: 89%
“…FMT also alleviated Paclitaxel-Induced Peripheral neuropathy in rats by interfering with the TLR4 pathway [80].…”
Section: Chemotherapy-induced Peripheral Neuropathymentioning
confidence: 89%
“…Gut microbiota serves as the intersection of immune, neural, endocrine, and metabolic signaling pathways and has become an intense focus of research [37]. Several studies have demonstrated that gut microbiota can modulate chemotherapy-induced neuropathic pain [38,39], even that the gut bacteria, rather than host genetics or physiology, are the primary determinants of PTX-induced pain based on a comparative study of paclitaxel responses in B6 and 129 germ-free reciprocally transplanted mice [40]. The study by Loman et al revealed the relationship among behavior, central and peripheral immune activation, and microbiota in PTX-treated mice [41].…”
Section: Discussionmentioning
confidence: 99%